ANALISIS PENGUNGKAPAN ENVIRONMENTAL, SOCIAL, GOVERNANCE (ESG) DAN PROFITABILITAS TERHADAP RETURN SAHAM - Yasmin Nur Maryam; Wahyu Helmy Dimayanti Sukiswo (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
This study aims to analyze ESG (Environmental, Social, and Governance) disclosure and profitability on stock returns in energy sector companies listed on the Indonesia Stock Exchange. The method used is a qualitative approach with literature review studies of 15 national and international indexed scientific publications from 2019 to 2024. The results show that ESG disclosures consistently have a positive impact on stock returns, as they can increase investor confidence, reduce information asymmetry, and reflect the company's commitment to sustainability. On the other hand, profitability measured through Return on Equity (ROE) has also been shown to have a significant influence on stock returns, as it reflects healthy financial performance and capital management efficiency. These two variables complement each other in increasing the attractiveness of the company in the eyes of investors. These findings underscore the importance of companies not only focusing on achieving profits, but also on transparent and accountable sustainability practices. The implications of this research are expected to contribute to investors, academics, and company management in making strong sustainability-based investment decisions and financial performance